3D-printed multifunctional chiral metamaterial with invariant sound absorption under large deformation and low-frequency vibration control - Jingjian Xu; Xiang Song; Boyang Zhao; Hanjie Yang; Dan Sui; Jie Zhou; Heye Xiao (Virtual and Physical Prototyping, 2024)
Acoustic metamaterials provide a distinctive route for reducing low-frequency noise and vibration; however, most are characterised by their singular functionality, e.g. sound absorption or vibration suppression. We present a 3D-printed multifunctional chiral metamaterial (MCM) with double helix structures inspired by cochlea and DNA for excellent acoustic, mechanical, vibration isolation and mitigation properties. By employing impedance matching, nearly perfect sound absorption can be obtained and kept invariably in the low-frequency range under strain from +25% to −25%, as confirmed by the standard impedance tube tests. The double helix structure provides versatile mechanical properties, including compressibility, stretchability, and recoverability. Excellent vibration isolation ability from 94 Hz and strong elastic wave attenuation performance between 199 and 254 Hz based on bandgap strategy are demonstrated by isolation and mitigation vibration tests and simulations. This 3D printed structure presents a promising solution for multipath noise control, setting a paradigm for biologically inspired multifunctional materials.